Understanding the interaction of assessment, learning and context: Insights from Singapore. Issue 1 (2nd January 2021) - Heng, Tang T.; Song, Lynn; Tan, Kelvin
ABSTRACT: Background: Assessment for learning (AfL) discourses and practices have gained popularity globally, as educational policies and ideas are transferred across borders. An important area of investigation is how AfL may be construed and enacted differently, according to context. Purpose: By examining how teachers in Singapore understand and use AfL – a core principle embedded within differentiated instruction – this study explores how context influences assessment, learning and teaching beliefs and practices. Method: As part of a larger study of how 10 public school teachers in Singapore understand and use differentiated instruction, the research reported here adopted a qualitative approach to elucidate teachers' lived experiences. Data, which were analysed thematically, included 10 questionnaires, 30 semi-structured interviews, 39 lesson observation logs and pre- and post-lesson observation interviews. Findings: The analysis identified three themes: (i) teaching and learning for Assessment of Learning (AoL) rather than AfL, (ii) teacher-directed rather than learner-driven AfL practices and (iii) behaviourist approaches in teaching and assessment practices. The finding suggested that teachers in Singapore face tensions as personal beliefs and practices around teaching, learning and assessment collide and/or coexist with their sociocultural and educational contexts. Conclusions: Rather than assuming that educational ideas like AfL are acontextual or represent a 'best practice' that transfers easily across countries, scholars, policymakers and educators would benefit from considering more fully how AfL is a 'situated' concept, and reflecting more deeply on the complex interplay between source and destination contexts.